Hypothalamic DNA methylation in rats with dihydrotestosterone‐induced polycystic ovary syndrome: effects of low‐frequency electro‐acupuncture. Issue 12 (23rd October 2018) - Cui, Peng; Ma, Tong; Tamadon, Amin; Han, Sha; Li, Bing; Chen, Zheyi; An, Xiaofei; Shao, Linus R.; Wang, Yanqing; Feng, Yi
Abstract : New Findings: What is the central question of this study? What is the role of hypothalamic DNA methylation in the development of polycystic ovary syndrome (PCOS) and the response to electro‐acupuncture treatment. What is the main finding and its importance? Global DNA methylation and expression of DNA methyltransferases (DNMTs) were increased in PCOS‐like rats, and electro‐acupuncture (EA) decreased global DNA methylation and DNMT3b expression. Pyrosequencing showed that the DNA methylation of some PCOS candidate genes was changed in the PCOS and PCOS+EA groups, suggesting that hypothalamic DNA methylation plays an important role in the development of PCOS and in mediating the effects of electro‐acupuncture treatment. Abstract: Polycystic ovary syndrome (PCOS) is a common reproductive and endocrine disease of unknown aetiology. Recently, epigenetic studies focusing on DNA methylation in PCOS have received much attention, but the mechanisms are still unclear. In the present study, we used the 5α‐dihydrotestosterone‐induced PCOS‐like rat model and treated the rats with electro‐acupuncture (EA). Rats were randomly divided into four groups – controls, diet‐induced obesity, PCOS and PCOS+EA. We examined the reproductive, metabolic and behavioural phenotypes, validated the effect of EA, and explored the role of hypothalamic DNA methylation by analysing the methylation of global DNA and selected candidate genes. The PCOS rats presented with reproductive dysfunctions such as lack of regular oestrous cyclicity, metabolic disorders such as increased body weight and insulin resistance, and depression and anxiety‐like behaviours. EA improved the reproductive functions, decreased body weight and improved experimental depressive behaviour. Furthermore, global DNA methylation and the expression of DNA methyltransferases (DNMTs) were increased in PCOS rats compared to the control group, and EA decreased the global DNA methylation and the expression of DNMT3b. In addition, pyrosequencing showed that the DNA methylation of certain CpG sites in targeted genes ( Plcg1, Camk2b, Esr2 and Pgr ) was increased in the PCOS group, but the DNA methylation of Camk2b and Ar was decreased after EA treatment. These results indicate that hypothalamic DNA methylation might be correlated with the development of PCOS and that EA has an effect on hypothalamic DNA methylation in PCOS rats. Abstract :